Installation of solar power plant as power supply for street lighting in livestock area - Reza Sarwo Widagdo; Puji Slamet; Aris Heri Andriawan; Izzah Aula Wardah (University of Merdeka Malang, 2023)
Sajen Village, in Pacet District, Mojokerto, already has a Village-Owned Enterprise (BUMDes) that is primarily involved in the management of livestock and agricultural products because has village treasury land. Farms with cows and goats are administered by cooperatives of farmers. Even though there is always a livestock supervisor on guard, one of the farm locations closest to the village hall uses makeshift lighting and has a low level of security. This is due to the limited electrical energy which is still sourced from the village hall. In addition, human resources in Sajen village also need to improve their soft skills and hard skills to develop the village and keep abreast of current issues. This initiated the idea of building an independent power plant in the livestock area as a useful energy source for village lighting and security. Off-grid system was built in the livestock area and has been successfully utilized to supply energy for the lighting and security sector in the livestock area. Off-grid systems refer to energy sources that are different from those used by the state power utility. Solar power plant also contributes a percentage of clean energy use in village areas and can be a pilot for further development.